Caracterización en la tenencia de gatos y su relación con anormalidades comportamentales evaluado en tutores de la universidad Antonio Nariño (2022)
The domestic cat is adopted as a pet in millions of homes and can be considered one of the most popular companion animals in the world (Plantinga et to the. 2011). Since cats descend from a territorial and solitary ancestor, their tendency inherited is to be antagonistic towards all animals larger than its typical prey and although domestication has reduced this phenomenon, the cat still depends more on the security of their territory than from psychological attachments to people or other cats (Sarah Heath, 2013)